Appropriate care for orthopedic patients: effect of implementation of the Clinical Practice Guideline for Diagnosis and Treatment of Subacromial Pain Syndrome in the Netherlands. (4th May 2019) - Veen, Egbert J D; Stevens, Martin; Koorevaar, Cornelis T; Diercks, Ron L
Abstract : Background and purpose — The multidisciplinary Clinical Practice Guideline for diagnosis and treatment of subacromial pain syndrome (SAPS) was created in 2012 by the Dutch Orthopedic Association. In brief, it stated that SAPS should preferably be treated nonoperatively. We evaluated the effect of the implementation of the guideline on the number of shoulder surgeries for SAPS in the Netherlands (17 million inhabitants). Patients and methods — An observational study was conducted with the use of aggregated data from the national database of the Dutch Health Authority from 2012 to 2016. Information was collected on patients referred to and seen at orthopedic departments. Data from the following Diagnoses Related Groupings were analyzed: 1450 (tendinitis supraspinatus) and 1460 (rotator cuff tear). Results — In 2016 fewer patients were diagnosed with tendinitis supraspinatus than in 2012—a decrease from 49, 491 to 44, 662 (10%). Of the patients diagnosed with tendinitis, 14% were treated surgically in 2012; this number dropped to 9% by 2016. More patients with a rotator cuff tear were diagnosed in 2016 than in 2012, an increase from 17, 793 to 23, 389 (32%), fewer were treated surgically: 30% in 2012, compared with 25% in 2016. Interpretation — After introducing the multidisciplinary Clinical Practice Guideline "Diagnosis and treatment of subacromial pain syndrome, " a decrease in shoulder surgeries for related diagnoses was observed in the Netherlands. The introduction and dissemination of this guideline seems to have contributed to the implementation of more appropriate health care and prevention of unnecessary surgeries.